2005
DOI: 10.2151/sola.2005-047
|View full text |Cite
|
Sign up to set email alerts
|

Efficiently Constraining Climate Sensitivity with Ensembles of Paleoclimate Simulations

Abstract: We use a recently-developed efficient probabilistic estimation technique to estimate the sensitivity of the Earth's temperature to a doubling of atmospheric carbon dioxide. The method is based on the ensemble Kalman filter which we apply to the CCSR/NIES/ FRCGC AGCM (the atmospheric component of MIROC 3.2) at T21L20 resolution coupled to a slab ocean. The method combines prior beliefs about the model, with observational data, to simultaneously estimate 25 model parameters in an efficient and objective manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 14 publications
(23 reference statements)
5
90
0
Order By: Relevance
“…For example, some studies used potentially observable information (such as the mean climate state [26] or the amplitude of the present-day seasonal cycle [19]) within these ensembles to attempt to find ECs on ECS, which could then be used without a first-order dependency on the sampling prior. Annan et al [1] used an ensemble Kalman filter approach together with PPE simulations of the last glacial maximum using the MIROC model, using LGM temperatures as an EC.…”
Section: Constraining Perturbed Ensemble Outputmentioning
confidence: 99%
“…For example, some studies used potentially observable information (such as the mean climate state [26] or the amplitude of the present-day seasonal cycle [19]) within these ensembles to attempt to find ECs on ECS, which could then be used without a first-order dependency on the sampling prior. Annan et al [1] used an ensemble Kalman filter approach together with PPE simulations of the last glacial maximum using the MIROC model, using LGM temperatures as an EC.…”
Section: Constraining Perturbed Ensemble Outputmentioning
confidence: 99%
“…Although the CS of MIROC5 PPE is low (2.2-3.2°C), the CS within the PPE of MIROC3 ASGCM (an old version of MIROC) is high ([4°C) (Annan et al 2005). Because many of the physical schemes in MIROC3 and MIROC5 differ (Watanabe et al 2010), it is not clear which schemes are largely responsible for determining the structural dependency.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…However, these wide ranges in CS are not universal. The PPEs used versions of the CAM3 GCM (Jackson et al 2008;Sanderson 2011) and the EGMAM GCM (Niehörster and Collins 2009) consistently yielded a CS of less than 3°C, whereas the PPEs of MIROC3 produced a CS greater than 4°C (Annan et al 2005;Yokohata et al 2010;Yoshimori et al 2011). The distributions of CS in PPEs are contingent upon the model structures as well as the experimental design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We define a comprehensive cost function which takes into account seasonality and incorporates variables representing different aspects of the climate system. As well as using present day observations in our cost function, we choose to include a proxy for the climate of the LGM, in part because our model is particularly useful for paleoclimate studies and also because the LGM has been shown to provide additional constraint for the climate sensitivity of the models (Edwards et al 2007;Annan et al 2005c). After briefly describing the model in Sect.…”
Section: Introductionmentioning
confidence: 99%